ANALISIS PRODUKTIVITAS DENGAN MENGGUNAKAN METODE AMERICAN PRODUCTIVITY CENTER DI CV. CUPU ARTAMA JAYA, JOMBANG, JAWA TIMUR - Dhita Morita Ikasari; Badaruzzaman Arya Dermawan; Panji Deoranto (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
CV. Cupu Artama Jaya is a chicken slaughterhouse managed by a private sector, located in Jombang, East Java. So far, CV. Cupu Artama Jaya has never measured productivity, but only evaluated financial benefits. This study aims to analyze the productivity index, profitability index and price repair index at CV. Cupu Artama Jaya. The method used in this research is the American Productivity Center (APC). APC is a method that compares historical data with current data to determine the level of productivity and company profitability. The historical data used in this study are March 2019 - February 2020. The results show that the lowest productivity index value is energy input of 69.975 and the highest productivity index is also energy input of 170.221. The lowest profitability index was energy input of 69.976 and the highest profitability index was also energy input of 170.283. The lowest price improvement index occurred in July 2019 and September 2019 at 0.998, while the highest price improvement index value occurred in February 2020 with a value of 1.002. Suggestions to increase productivity and profitability at CV. Cupu Artama Jaya includes adding job descriptions to employees to monitor energy use, setting quality standards and price limits for chickens received from breeders, arranging agreements related to the number of chicken orders with breeders, holding training for new workers, implementing sanctions related to employee discipline and considering apply overtime hours to reach production targets.